Spermatic Cord Lipoma—A Review of the Literature - Köckerling, Ferdinand; Schug-Pass, Christine (Frontiers in Surgery, 2020)
Introduction A spermatic cord lipoma is found in 20-70% of all inguinal hernia repairs. The clinical picture of an inguinal hernia with bulging and pain but without an actual indirect hernia sac may become manifest in up to 8% of these cases. Missed spermatic cord lipoma can result in recurrence or pseudo-recurrence. This review presents the relevant literature on this topic. Material and methods A systematic search of the available literature was performed in February 2020 using Medline, PubMed, Google Scholar, Scopus, Embase, Springer Link, and the Cochrane Library, as well as a search of relevant journals and reference lists. 42 publications were identified as relevant for this topic. Results Spermatic cord lipoma seems to originate from preperitoneal fatty tissue within the internal spermatic fascia in topographical proximity to the arteries, veins, lymphatics, nerves and deferent duct within the spermatic cord. Reliable diagnosis cannot be made clinically, but rather with ultrasound, CT or MRI. In the absence of a real hernia sac a spermatic cord lipoma is classified as a lateral inguinal hernia with a defect size < 1.5 cm according to the European Hernia Society (EHS LI). Missed or inadequately treated spermatic cord lipoma results in recurrence or pseudo-recurrence. Since spermatic cord lipoma obtains its vascular supply from the preperitoneal space, it can be reduced or resected. Conclusion Spermatic cord lipoma is a common finding in inguinal hernia repairs and must be properly diagnosed and treated with care respecting the anatomy of the spermatic cord.